Organic spectroscopy : - Mohan, Jag (Alpha Science International Ltd., 2000)
this book offers a general introduction to electromagnetic radiation and molecular spectroscopy. In addition to the usual topics on IR, UV, NMR and Mass spectrometry, it includes substantial material on the currently useful techniques such as FT-IR, FT-NMR 13C-NMR, 2D-NMR, GC/MS, FAB/MS, Tendem and Negative Ion Mass Spectrometry for students engaged in advanced studies. Finally it gives a detailed account on Optical Rotatory Dispersion (ORD) and Circular Dichroism (CD). The book also provides Description of Harmonic and Anharmonic Molecular Vibrations in Chapter on Infrared Spectroscopy · Shielding and Deshielding of protons in charged species and concepts of positive and negative coupling constants highlighted in chapter on Nuclear Magnetic Resonance Spectroscopy